Clinical Epidemiology of Adults With Moderate Traumatic Brain Injury*. Issue 5 (May 2018) - Watanitanon, Arraya; Lyons, Vivian H.; Lele, Abhijit V.; Krishnamoorthy, Vijay; Chaikittisilpa, Nophanan; Chandee, Theerada; Vavilala, Monica S.
Abstract : Objectives: To characterize admission patterns, treatments, and outcomes among patients with moderate traumatic brain injury. Design: Retrospective cohort study. Setting: National Trauma Data Bank. Patients: Adults (age > 18 yr) with moderate traumatic brain injury ( International Classification of Diseases, Ninth revision codes and admission Glasgow Coma Scale score of 9–13) in the National Trauma Data Bank between 2007 and 2014. Interventions: None. Measurement and Main Results: Demographics, mechanism of injury, hospital course, and facility characteristics were examined. Admission characteristics associated with discharge outcomes were analyzed using multivariable Poisson regression models. Of 114, 066 patients, most were white (62%), male (69%), and had median admission Glasgow Coma Scale score of 12 (interquartile range, 10–13). Seventy-seven percent had isolated traumatic brain injury. Concussion, which accounted for 25% of moderate traumatic brain injury, was the most frequent traumatic brain injury diagnosis. Fourteen percent received mechanical ventilation, and 66% were admitted to ICU. Over 50% received care at a community hospital. Seven percent died, and 32% had a poor outcome, including those with Glasgow Coma Scale score of 13. Compared with patients 18–44 years, patients 45–64 years were twice as likely (adjusted relative risk, 1.97; 95% CI, 1.92–2.02) and patients over 80 years were five times as likely (adjusted relative risk, 4.66; 95% CI, 4.55–4.76) to have a poor outcome. Patients with a poor discharge outcome were more likely to have had hypotension at admission (adjusted relative risk, 1.10; 95% CI, 1.06–1.14), lower admission Glasgow Coma Scale (adjusted relative risk, 1.37; 95% CI, 1.34–1.40), higher Injury Severity Score (adjusted relative risk, 2.97; 95% CI, 2.86–3.09), and polytrauma (adjusted relative risk, 1.05; 95% CI, 1.02–1.07), compared with those without poor discharge outcomes. Conclusions: Many patients with moderate traumatic brain injury deteriorate, require neurocritical care, and experience poor outcomes. Optimization of care and outcomes for this vulnerable group of patients are urgently needed. Abstract : Supplemental Digital Content is available in the text.